Feasibility of Project-Based Biology Learning Design for Utilizing Agro-Industrial Waste to Improve Eco-Literacy of High School Students - Eurika, Novy; Priantari, Ika; Prafitasari, Aulya Nanda; Suryani, Anisa Dea (Bioeducation Journal, 2024)
Ecoliteracy (ecological literacy) refers to an understanding of how humans can interact with one another as well as with nature, and how this contributes to sustainability. The purpose of this study is to describe the process and results of validating the development of a project-based Biology learning design using agro-industrial waste to improve high school students' ecoliteracy levels. This learning design development research was carried out using the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate), which was limited to the development stage. The learning design includes teaching modules, E-LKPD, and ecoliteracy assessment tools (test questions and questionnaires). Data on the validity of the learning design were collected using expert validation sheets and analyzed descriptively using the development product criteria. The average score for the learning design validation test by material and learning design experts and users (teachers) was 92.4; 82.6; 92.4; and 95.8. The test included validation of teaching modules, E-LKPD, ecoliteracy questions, and ecoliteracy questionnaires. Based on the criteria for the feasibility of teaching materials, the average value falls into the "very valid" category and can be used to teach grade X high school biology on environmental change.